The application of Foucault's disciplinary power to microcredit programmes in two villages of Sylhet, Bangladesh. Issue 1 (2nd January 2020) - Al-Amin, Md; Islam, Md Nazrul
ABSTRACT: This article aims to explore the loan recovery mechanisms of two internationally-reputed microcredit and development organisations in Bangladesh. The organisations are Grameen Bank and Bangladesh Rural Advancement Committee (BRAC). We conducted an institutional ethnography to study the phenomenon of loan recovery from the poor. Data were collected through in-depth interviews, case studies, informal discussion, and direct observation. Purposive sampling methods were adopted to select the respondents. We administered 49 intensive interviews, conducted case studies of 19 typical respondents, and had interview/informal conversations with four Grameen Bank and BRAC field staff. The study finds that both Grameen Bank and BRAC apply disciplinary power to the borrowers for the recovery of loans. Grameen Bank and BRAC bind poor women into programme discipline and oblige them to comply with institutional norms through formal credit practices. Institutions' rigid policies in relation to loan recovery exclude impoverished women, who do not comply with loan recovery requirements, from future participation in microcredit programmes. Borrowers having stable work and regular cash flow can reap longer-term benefits from microcredit and because they are able to repay loans and thus continue in the programmes. Exclusion for loan defaults thus acts as a punishment, which is rigidly practiced in these development institutions.